Kajian Mitigasi Bencana Abrasi Berbasis Partisipasi Masyarakat di Kawasan Pesisir Kecamatan Bonto Bahari Kabupaten Bulukumba - Andi Irul Trihadi; Risma Handayani; Nur Syam AS; Risnawati.K K (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2026)
The transformation of coastal areas in Indonesia is now at a critical point due to the acceleration of climate change that triggers sea level rise and the intensity of extreme hydrometeorological phenomena. As an archipelagic country with a coastline of more than 95,000 kilometers, Indonesia faces an existential challenge in protecting its coastal ecosystem from the threat of destructive abrasion. This study discusses the problem of coastal abrasion in Bonto Bahari District, especially in Sapolohe Village, which has eroded about 850 meters of coastline and threatened dozens of residents' homes and the livelihoods of coastal communities. Overlay analysis showed that Sapolohe had the highest level of abrasion risk (score 5.0), followed by Tanah Lemo (3.5) and Bira (3.0), while Benjala was classified as safe (score 0). The results of the Likert scale analysis show that the level of abrasion mitigation efforts is in the category of adequate (48.11%), with community knowledge (50.7%), the implementation of institutional programs (45%), and socio-cultural values (48.65%) still need to be improved. The mitigation efforts implemented include training, socialization, mangrove planting, and strengthening local socio-cultural values. A community participatory approach is considered important to create an effective and sustainable abrasion mitigation strategy in the coastal area of Bonto Bahari.